Impaired Microcirculation and Vascular Hemodynamics in Relation to Macrocirculation in Patients With Systemic Lupus Erythematosus - Svensson, Christina; Eriksson, Per; Bjarnegård, Niclas; Jonasson, Hanna; Strömberg, Tomas; Sjöwall, Christopher; Zachrisson, Helene (Frontiers in Medicine, 2021)
Abstract Introduction: Systemic lupus erythematosus (SLE) is associated with premature cardiovascular disease (CVD) and mortality, unexplained by traditional risk factors. Impairment of microcirculation and vascular hemodynamics may represent early signs of vascular affection. We hypothesized that studies of microcirculation and pulse waves may provide additional information, compared to ultrasound (US) alone, for the detection of early vascular disease in SLE. Methods: 60 well-characterized SLE-patients (52 women, 8 men; mean age 43.2±11.3 years) characterized by lupus nephritis (LN; n=20), antiphospholipid syndrome (APS; n=20) or skin and joint involvement (n=20) and 60 healthy controls were included. Microcirculatory peak oxygen saturation (OxyP) was evaluated using a novel combined laser Doppler flowmetry/diffuse reflectance spectroscopy method. Pulse waves were recorded in the radial artery by the aid of applanation tonometry in order to calculate central augmentation index (AIx75). Intima-media thickness (IMT) and plaque occurrence were evaluated using high frequency US, in carotid and central arteries. Results: Lower OxyP (84±8 % vs. 87±5 %, p=0.01) and higher AIx75 (17.3±13.9 % vs. 10.0±14.2 %, p=0.005) were seen in the SLE cohort. OxyP was inversely correlated with IMT in internal carotid artery (ICA), (R=-0.32, p=0.01). AIx75 correlated with IMT in common carotid artery (CCA), (R=0.36, p=0.005), common femoral artery (CFA), (R=0.43, p=0.001), and ICA (R=0.27, p=0.04). AIx75 correlated negatively with OxyP (R=-0.29, p=0.02). SLE-patients with plaque had lower OxyP values (80±8 % vs. 85±7 %, p<0.001) and higher AIx75 (23.0±11.6 % vs. 15.5±14.2 %, p<0.001) compared to those without plaque. Conclusion: Impaired microcirculation and vessel hemodynamics were observed in SLE. These methods correlated with IMT and plaque occurrence. The importance of early macro- and micro-circulatory vascular affection for increased risk of CVD in SLE will be followed-up in future studies. Key words: SLE, Microcirculation, Microvascular dysfunction, Augmentation Index, Ultrasound, IMT